2023
DOI: 10.1161/jaha.122.026295
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Year Outcomes With a Next‐Generation Left Atrial Appendage Device: Final Results of the PINNACLE FLX Trial

Abstract: Background The PINNACLE FLX (Protection Against Embolism for Non‐valvular AF [Atrial Fibrillation] Patients: Investigational Device Evaluation of the Watchman FLX LAA [Left Atrial Appendage] Closure Technology) trial evaluated the safety and efficacy of a next‐generation left atrial appendage closure device (WATCHMAN FLX; Boston Scientific, Marlborough, MA). At 1 year, the study met the primary end points of safety and anatomical efficacy/appendage closure. This final report of the PINNACLE FLX tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…Both of the trials suggested that LAA occlusion was non-inferior to DOACs on the composite endpoint event. Recently, next-generation Watchman FLX device also demonstrated favourable safety and efficacy outcomes for stroke prevention and improved certain limitations observed with the first-generation device, such as perforation risk and residual peridevice leak 41. Percutaneous LAA occlusion has been commonly used for stroke prevention, and the successful closure rate of percutaneous transcatheter LAA occlusion devices ranged from 91% to 98.5% 42–46.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Both of the trials suggested that LAA occlusion was non-inferior to DOACs on the composite endpoint event. Recently, next-generation Watchman FLX device also demonstrated favourable safety and efficacy outcomes for stroke prevention and improved certain limitations observed with the first-generation device, such as perforation risk and residual peridevice leak 41. Percutaneous LAA occlusion has been commonly used for stroke prevention, and the successful closure rate of percutaneous transcatheter LAA occlusion devices ranged from 91% to 98.5% 42–46.…”
Section: Methods and Analysismentioning
confidence: 99%
“…2 LAAO has become increasingly popular, affording >90% of treated patients the opportunity to avoid long-term anticoagulants (OACs), thereby lowering the risk of hemorrhagic stroke and other bleeding complications. [3][4][5] By nature of their age, comorbidities, and symptomatic status, nearly all TAVI candidates with atrial fibrillation have both an indication for OACs and an elevated bleeding risk.…”
Section: Article See P 734mentioning
confidence: 99%
“…In the present study by Doshi et al in this issue of Journal of the American Heart Association ( JAHA ), 4 the authors report the 2‐year safety and effectiveness outcomes from the PINNACLE FLX study. From an effectiveness perspective, the combined risk of ischemic stroke or systemic embolism at 2 years was 3.4%.…”
mentioning
confidence: 93%
“…At 1 year of follow‐up, the risks of ischemic stroke/systemic embolism and major bleeding were 3.1% and 7.9%, respectively. 3 , 4 …”
mentioning
confidence: 99%